The Influence of Motivation, Leadership and Productivity on Performance at PT. Perimex Perimex Village - Hepi; Ruth; Ester; Yovie Ernanda (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of motivation on employee performance at PT. Perimex, knowing the influence of leadership on employee performance at PT. Perimex, knowing the effect of productivity on the performance of employees of PT Perimex and knowing the effect of motivation, leadership and productivity simultaneously on the performance of employees of PT. Perimex is implemented at PT. Perimex with the population, namely all employees of PT. Perimex amounted to 96 people with saturated sampling technique using total sampling obtained a research sample of 96 people. As for the results of the research, partially obtained the value of motivation t count (X1) is 3.371 and the table value is 1.984 provided that the value of t count> t table (3.371> 1.984) and the value of sig <0.05 (0.001 <0.05), partially obtained the value of t count. Leadership (X2) is 3, Leadership and Productivity make a big contribution in explaining employee performance of 76.80% while the 23.20% chance is influenced by other factors outside of research. The conclusion of the study is that motivation has a significant effect on employee performance, leadership has a significant effect and is the dominant variable that affects employee performance, productivity has a significant effect on employee performance and simultaneously motivation, leadership and productivity have a significant effect on employee performance.